Respuesta :
Answer:
an = 26 -2(n -1)
Step-by-step explanation:
You want the explicit formula for the arithmetic sequence that starts 26, 24, 22, ....
Arithmetic sequence
The difference between successive terms of this sequence is ...
24 -26 = -2
The first term is 26.
The n-th term of an arithmetic sequence is given by the formula ...
an = a1 +d(n -1) . . . . . . a1 is the first term and d is the common difference
Using the values above, we have ...
[tex]\boxed{a_n=26-2(n-1)}[/tex]
__
Additional comment
This could be simplified to an = 28 -2n, if you like.
Answer:
Step-by-step explanation:
26, 24, 22
nth term
= a + d(n - 1)
= 26 - 2(n - 1)
= 26 - 2n + 2
= 28 - 2n